WHY DIDN’T YOU HELP? DISCOURSE ANALYSIS OF EMPATHY AND BYSTANDER BEHAVIOR AMONG YOUTH - Rahmi, Rahmi; Napitupulu, Lisfarika; Amita, Nindy; Lubis, Bahril Hidayat (Journal of Pragmatics and Discourse Research, 2025)
This study investigates the relationship between empathy and the bystander effect among adolescents. The increasing prevalence of passive observer behavior, particularly in emergency or distressing situations involving youth, underscores the importance of examining psychological factors such as empathy. Using a quantitative correlational design, this study collected data from 320 adolescents aged 15–21 in Pekanbaru, Indonesia. Participants completed standardized Likert-scale questionnaires measuring empathy and bystander effect tendencies. The data were analyzed using simple linear regression. The findings reveal a significant negative correlation between empathy and the bystander effect. Specifically, higher levels of empathy are associated with a lower tendency to engage in passive bystander behavior. These results support theoretical perspectives that emphasize the emotional and cognitive dimensions of empathy as crucial mechanisms in promoting prosocial action. The study suggests that enhancing empathy through targeted interventions could reduce passive behaviors in emergency situations and promote greater social responsibility among adolescents. Beyond statistical findings, this study has clear implications for character education and school-based interventions. Educators can integrate empathy-building activities into the curriculum through narrative exercises, role-play, and collaborative discussions that help students articulate moral reasoning. Teachers play a vital role in reshaping discourse patterns by encouraging students to critically examine common justifications for inaction, such as “someone else will help” or “I didn’t want to stand out.” By fostering reflective language and scenario-based discussions, schools can cultivate not only emotional competence but also discursive awareness that promotes social responsibility and civic courage among youth.